"Getting to Zero New HIV Infections in the Caribbean": Knowledge and Attitudes Toward Male Circumcision Among Adolescent Males in The Bahamas. Issue 4 (August 2019) - George, Clemon; Roberts, Robin; Deveaux, Lynette; Brennen, Delon F.P.; Read, Stanley E.
Male circumcision (MC) plays a significant role in reducing new HIV infections, particularly in high prevalence countries. This cross-sectional study assesses the prevalence of MC and attitudes toward MC among youth aged 15–18 years in The Bahamas, a medium HIV prevalence country. The survey included 797 young men who completed a questionnaire on MC. Data analyses included chi-squared tests. The self-reported prevalence of MC among youth was 16.7% (121/759). Most of the circumcised youth were circumcised as infants, 84% (107/121) were pleased with their circumcision, and 71% would recommend it to others. For uncircumcised youth, 35% (189/533) would consider voluntary male circumcision (VMC) and 26% would recommend MC to others. In all scenarios, circumcised youth were more likely to be positive about MC. Among uncircumcised young men, being older (17–18 years compared to 15–16 years) was the only variable statistically associated with considering MC or recommending MC. After being presented with information on the benefits of MC for HIV prevention, the number of men who were positive about MC increased. Most of the young men in this cohort would consider VMC for reducing HIV incidence. Also, many stated that, if they had a male child, they would have him circumcised. The attitudes of these youth emphasize the need to provide information on HIV in addition to general health benefits of MC if there were to be a sustainable MC program within this population.